2011
DOI: 10.5194/acp-11-7617-2011
|View full text |Cite
|
Sign up to set email alerts
|

HOCl and Cl<sub>2</sub> observations in marine air

Abstract: Abstract. Cl atoms in the marine atmosphere may significantly impact the lifetimes of methane and other hydrocarbons. However, the existing estimates of Cl atom levels in marine air are based on indirect evidence. Here we present measurements of the Cl precursors HOCl and Cl2 in the marine boundary layer during June of 2009 at the Cape Verde Atmospheric Observatory in the eastern tropical Atlantic. These are the first measurements of tropospheric HOCl. HOCl and Cl2 levels were low in air with open ocean back t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 46 publications
5
122
0
Order By: Relevance
“…Previous studies have observed the production of Br 2 from HOBr and HOCl even on relatively clean inlets, apparently without formation of BrCl (Neuman et al, 2010;Lawler et al, 2011). By analogy, inlet I 2 production without concomitant ICl or IBr production may be possible.…”
Section: Observations Of Daytime I 2 : Positive Artifactmentioning
confidence: 99%
“…Previous studies have observed the production of Br 2 from HOBr and HOCl even on relatively clean inlets, apparently without formation of BrCl (Neuman et al, 2010;Lawler et al, 2011). By analogy, inlet I 2 production without concomitant ICl or IBr production may be possible.…”
Section: Observations Of Daytime I 2 : Positive Artifactmentioning
confidence: 99%
“…Inorganic chlorine observations are better constrained, although concurrent measurements of Cl 2 and HOCl, especially under semi-polluted conditions Lawler et al, 2009Lawler et al, , 2011, are difficult to reconcile and BrCl, which the models predict as one of the major components of total Br, has not been detected in marine environments. It is unclear whether the model-measurement disagreements are due to instrumental issues or to some fundamental problem in our understanding of the chemistry, particularly in the aqueous phase , but they make it difficult to accurately assess the effect of chlorine and bromine on ozone under unpolluted and semi-polluted conditions.…”
Section: Halogensmentioning
confidence: 99%
“…Isoprene SOA formation initiated by ozone (O 3 ), nitrate (NO 3 ), and hydroxyl (OH) radicals has been studied extensively and is estimated to account for 6-30 Tg yr −1 of the global aerosol budget (Brégonzio-Rozier et al, 2015;Claeys, 2004;Guenther et al, 2006;Kroll et al, 2006;Surratt et al, 2006Zhao et al, 2015), but the importance of isoprene SOA formation within the marine boundary layer (MBL) remains highly disputed in the literature (Arnold et al, 2009;Bikkina et al, 2014;Fu et al, 2011Fu et al, , 2013Gantt et al, 2010Gantt et al, , 2015Hu et al, 2013;Luo and Yu, 2010;O'Dowd and de Leeuw, 2007). Although the production of reactive chlorine species such as Cl 2 and HOCl has been observed within the MBL (Lawler et al, 2011), little is known about SOA from chlorine-initiated oxidation of isoprene.…”
Section: Introductionmentioning
confidence: 99%